Knee Hyperextension as a Predictor of Failure in Revision ACL Reconstruction: A Prospective Cohort Study. Issue 7 (18th July 2016) - Cooper, Daniel E.; Dunn, Warren R.; Wright, Rick W.; Haas, Amanda; Huston, Laura J.
Objectives: We studied the minimum 2 year follow-up outcomes in an ACL revision cohort. The hypothesis is that knees that hyperextend will have a worse outcome and greater odds of graft failure than knees that do not hyperextend. The null hypothesis is that there is no difference in outcomes or graft rupture between the two groups. Methods: Revision ACL reconstruction patients were identified and prospectively enrolled between 2006 and 2011. Data collected included baseline demographics, surgical technique and pathology, and a series of validated patient reported outcome instruments (IKDC, KOOS, WOMAC, and Marx activity rating score). Patients were followed up for 2 years, and asked to complete the identical set of outcome instruments. A regression model using graft failure as the dependent variable included graft type, age, and hyperextension greater than or equal to 5 degrees yes/no (HE) in order to assess these potential surgical risk factors for clinical outcomes 2 years after revision ACL reconstruction. Results: There were 1, 145 subjects included in the analyses. The median age of the cohort was 26 (IQR= 20, 35), and 58% were male. The proportion that were enrolled for their first revision surgery was 88%, their second 10%, and third or greater 2%. The number of subjects categorized as HE was 375 (33%). The median age of subjects that failed was 18, compared to 26 for those with intact grafts. All three variables included in our regression model were significant predictors of graft failure: younger age, inter-quartile range odds ratio (IQROR) = 3.32 (95%CI 1.5, 7.2) p= 0.002; use of allograft OR = 3.1 (95%CI 1.4, 6.9) p= 0.01, and HE 2.1 (95%CI 1.02, 4.42) p= 0.04. Conclusion: The MARS Study Group has previously reported that young age and the use of allograft as a graft source are independent predictors (over 3X odds ratio) of graft rupture after revision ACLR. This study found that knee hyperextension greater than or equal to 5 degrees is present in 1/3 of patients who undergo revision ACLR. HE is also an independent predictor of graft failure after revision ACLR. This is the first study to investigate and confirm knee physiologic hyperextension as a risk factor (over 2X odds ratio) of graft rupture in ACL surgery. Future reports on ACL reconstruction results should separately evaluate the group of knees that hyperextend 5 degrees or more as compared to those that do not.